Two-step human–environmental impact history for northern New Zealand linked to late-Holocene climate change. (July 2018) - Newnham, Rewi; Lowe, David J; Gehrels, Maria; Augustinus, Paul
Following resolution of a long-standing debate over the timing of the initial settlement of New Zealand from Polynesia (late 13th century), a prevailing paradigm has developed that invokes rapid transformation of the landscape, principally by fire, within a few decades of the first arrivals. This model has been constructed from evidence mostly from southern and eastern regions of New Zealand, but a more complicated pattern may apply in the more humid western and northern regions where forests are more resilient to burning. We present a new pollen record from Lake Pupuke, Auckland, northern New Zealand, that charts the changing vegetation cover over the last 1000 years, before and after the arrival of people. Previous results from this site concurred with the rapid transformation model, although sampling resolution, chronology and sediment disturbance make that interpretation equivocal. Our new record is dated principally by tephrochronology together with radiocarbon dating and includes a cryptotephra deposit identified as Kaharoa tephra, a key marker for first settlement in northern New Zealand. Its discovery and stratigraphic position below two Rangitoto-derived tephras enables a clearer picture of environmental change to be drawn. The new pollen record shows an early phase (step 1) of minor, localised forest clearance around the time of Kaharoa tephra ( c . 1314 AD) followed by a later, more extensive deforestation phase (step 2) commencing at around the time of deposition of the Rangitoto tephras ( c . 1400–1450 AD). This pattern, which needs to be corroborated from other well-resolved records from northern New Zealand, concurs with an emerging hypothesis that the 'Little Ice Age' had a significant impact on pre-European Māori with the onset of harsher conditions causing a consolidation of populations and later environmental impact in northern New Zealand.